Variations in melatonin levels in preterm and term human breast milk during the first month after delivery - Yishi Qin; Weiyang Shi; Jialu Zhuang; Yu Liu; Lili Tang; Jun Bu; Jianhua Sun; Fei Bei (2019)
Abstract The objectives of the present study were to examine the dynamic changes in breast milk melatonin throughout the course of lactation and to explore factors associated with changes in melatonin concentrations and rhythms in both preterm and term breast milk. Breast milk was collected sequentially at 03:00, 09:00, 15:00, and 21:00 in one day. Melatonin was analyzed in 392 breast milk samples from 98 healthy nursing mothers at 0 to 30 days postpartum. In both preterm and term breast milk, the melatonin concentration presented a circadian rhythm with the acrophase at around 03:00. Subgroup analysis showed the peak melatonin concentrations differed significantly across lactation stages, with the highest concentration in the colostrum, followed by transitional and mature breast milk. At 03:00, preterm breast milk had a higher concentration of melatonin than term breast milk in the colostrum (28.67 pg/mL vs . 25.31 pg/mL, p < 0.022), transitional breast milk (24.70 pg/mL vs . 22.55 pg/mL), and mature breast milk (22.37 pg/mL vs . 20.12 pg /mL). Further studies are warranted for their roles and significance on melatonin in breast milk in nutrition and metabolism of neonates.